Small- and medium-sized enterprises (SME) growth and financing sources: Before and after the financial crisis. (10th January 2021) - Serrasqueiro, Zélia; Leitão, João; Smallbone, David
Abstract: In this study, the empirical evidence regarding small- and medium-sized enterprises' (SMEs) growth determinants allows us to conclude that: (1) stimulating factors are cash flow and gross domestic product; (2) restrictive factors are: debt, firm size, age of the firm and the interest rate; and (3) in the period after 2008, the financial crisis and implementation of austerity measures, in the Portuguese context, produced a negative effect on SME growth. In the period 2008–2012, that is, after the beginning of the financial crisis, cash flow had less importance, while debt was found to have a stronger negative effect on SME growth, compared with the pre-crisis period.